Experimental Models of Multiple Sclerosis - Lavi, Ehud.; Lavi, Ehud.; Constantinescu, Cris S.; Constantinescu, Cris S. (Springer US : Imprint: Springer, 2005)
Multiple Sclerosis (MS) is an enigmatic immune mediated disease of the central nervous system that affects about 350,000 individuals in the US, and many more around the world. The mechanism of this disease is largely unknown and there is no cure for it. However, there are several well-characterized experimental animal models that help us understand and speculate about potential mechanisms of pathology in this disease. Many of the experimental therapies designed for this disease rely on testing the drugs in animal models before using it in clinical trials. This book combines for the first time the different experimental models for MS (including immune-mediated and viral) under one roof, and highlights aspects that are different or shared among these experimental models. It’s aim is to improve our understanding of this devastating disease and help us think about potential additional therapies for it. Experimental Models of Multiple Sclerosis will be an important reference for neuroscientists, neurologists, immunologists, microbiologists (especially virologists) and pathologists (especially neuropathologists). Health professionals involved with MS, and medical students will also benefit from this book.